Neotectonic control of mud diapirism in the Cartagena region, Colombia (2009)
Major structures of the Sinu and San Jacinto Deformation Belts (SSJDB)characterize the area and are represented by anticline and synclinal folds, NE-SW high angle thrust-faults, NW-SE left-lateral strike-slip faults and E-Wright-lateral strike-slip faults. Locally, there are diapiric features like mud volcanoes, sometimes associated to gas/oil seeps, previously attributed to fold structures orthogonal to regional compression based on geophysical data. In this case study, we identified a close relationship between diapiric features and morphostructural lineaments on the land area as well as on the continental shelf, mainly denoted by E-W and WNW-ESE direction structures. Seismic information also allowed the identification of a relationship between the lower mud level underlying the tertiary sedimentary sequence and pliocene-pleistocene diapiric features. The inversion stress analysis indicates that the E-W / NW-SE structures are related to a WNW-ESE regional compressional stress, so implying that the E-W structures are right-lateral strike-slip faults and the NW-SE structures are reactivated left-lateral strike-slip faults. In both cases, a normal component was detected and that suggests a transtractive character to these structures. The presence of mud volcanoes indicates that the lower mud levels submitted to overpressurization help to generate or/and reactivate secondary fractures and faults associated to the NW compression related to the E-Wdextral transcurrent binary. The E-W and WNW-ESE dextral transcurrent faults and the NW-SE sinistral transcurrent faults, which control the mud diapirism, act as fluid-conducting surfaces - or leaky faults - that must be taken into account on the studies aiming the characterization of hydrocarbon migration processes in the SSJDB.